Local goal-based governance: a novel approach to environmental sustainability in China? - Jing Xu; Chuntian Lu; Ning Xiang; Meng Liu; Yichen Ma (Environmental Research Communications)
The recent emergence of goal-based governance at global scale may be considered as a new approach to enhance environmental sustainability at local level. This article examines how local goal-based governance actually unfolds with a focus on its fundamental features and effectiveness. We first build a conceptual framework for local goal-based governance which consists of three key elements: nature of problem, setting the goals, and achieving the goals. It provides a set of theoretical propositions: (1) the problems with two defining features are more amendable to goal-setting strategies, (2) setting a specified, practical, and learning-focused goal structure as the key premise, (3) goal attainment is built around a campaign-mode experimentation to try and find out locally appropriate approaches, a double-layered engagement between civil society and statutory institutions, and a system to track the goals through quantitative and qualitative measures. Based on semi-structured interviews and documents analysis, we adopt a case study of Chinese local waste management to test the theory and explain the unique process of local goal-based governance. This article also discusses how local goal-based governance differs from the traditional rule-based governance and further explores how these two governance strategies interact with each other to realize local changes. We highlight two complementary effects: enabling and compensating. Local goal-based governance has unique strengths to compensate for the weakness of rule-based system in promoting civic engagement; and meanwhile rule-based governance creates favorable social conditions within which local goal-based governance is initiated and developed. The inherent challenges and limitations of local goal-based governance are also discussed.